The Transition from Environmental Management to Environmental Governance: Towards A Normative and Procedural Framework for Achieving Sustainable Development - Eldeqen, Ahmed (The Arab Journal of Administration, 2019)
The aims of this study is to try to arrive at a normative and procedural framework for the transition from environmental management to environmental governance, to try to define the environmental governance system and to identify the close relationship between environmental governance and sustainable development. The study uses the methodology of System Analysis and the method of Inductive Analysis. The study is based on a key hypothesis: the shift from environmental management to environmental governance leads to sustainable development. The main hypothesis is divided into four sub-hypotheses, as follows: The transition requirements(inputs) from environmental management to environmental governance contribute to sustainable development, The transition processes from environmental management to environmental governance contribute to sustainable development, The transition outputs from environmental management to environmental governance are considered the main dimensions of sustainable development and The transition outcomes from environmental management to environmental governance are reflected in the inputs of environmental governance ( as a feedback). The results of this study may have implications for policy makers.